Diagnosis of mycobacterium avium complex infection utilizing metagenomics next-generation sequencing: a case report - Li, Hongli; Wei, Luqing; Li, Fenge (Frontiers in Medicine, 2023)
Mycobacterium avium-intracellulare complex (MAC) is a type of nontuberculous mycobacteria (NTM) and is associated with underlying pulmonary diseases, such as chronic obstructive pulmonary disease, bronchiectasis, chronic aspiration or recurrent pneumonia, inactive or active tuberculosis, pneumoconiosis, and bronchogenic carcinoma. The risk factors for NTM-PD include host, drug, and environmental factors. In this report, we present the case of a 61-year-old man who developed bilateral lung nodules and was experiencing severe hemoptysis. The repeat acid-fast bacilli test performed on both sputum and bronchoalveolar lavage fluid (BALF) samples showed a negative result, as did the GeneXpert test. We employed metagenomic next-generation sequencing (mNGS) to analyze the lung nodule and BALF samples collected from the patient. Both samples tested positive for MAC within 3 days. In addition, traditional MAC culture, conducted for 2 months, confirmed the growth of MAC in the patient’s BALF. Then, the patient was treated accordingly. Following treatment, a high-resolution chest computed tomography scan revealed a significant reduction in lung nodules of the patient after 2 months. These results indicate that MAC-associated lung nodules were responsible for the patient’s symptoms, emphasizing the need for vigilance in diagnosing MAC infection in the patient without predisposing conditions. Furthermore, these results highlight the potential utility of mNGS as a promising rapid diagnostic tool for MAC infection and its potential role in the diagnosis of NTM disease.